A New Dibenzyl from Pleione bulbocodioides - Liu, Xin-Qiao; Yuan, Qiao-Yu (Asian Journal of Chemistry, 2013)
A new dibenzyl named 6'-(3''-hydroxyphenethyl)-4'-methoxydiphenyl-2,2',5-triol and two known compounds were isolated from the tubers of Pleione bulbocodioides (Franch.) Rolfe. Their structures were elucidated by spectroscopic methods.